63.9k views
25 votes
Someone please help at your earliest convenience I would really appreciate it.

Someone please help at your earliest convenience I would really appreciate it.-example-1
User FilmJ
by
5.5k points

1 Answer

7 votes

Answer:

Explanation:

Let the equation is, y = x² + bx + c

Here, b = Sum of the roots

And c = multiplication of the roots

Roots of the equation are (5 + 2i) and (5 - 2i).

Step 1,

Sum of the roots 'b' = (5 + 2i) + 95 - 2i)

b = 10

Step 2,

Multiplication of the given roots = (5 - 2i)(5 + 2i)

= 5² - (2i)²

= 25 + 4

= 29

Step 3

Therefore, equation of the quadratic function will be,

y = x² + 10x + 29

User Sasi Kathimanda
by
5.9k points